Description of the female and male of Mycetarotes carinatus (Hymenoptera: Formicidae) - Mayhé-Nunes, Antonio José (2004)
We describe the female and male of the Neotropical fungus-growing ant Mycetarotes carinatus, hitherto only known from type locality, Rio de Janeiro state, Brazil, based on samples of workers. The sexual forms were obtained from a nest maintained in the laboratory. The samples found in Minas Gerais state, expand the geographic distribution of the species. We illustrate the external architecture of the nest of M. carinatus